Cyclosporine -induced Kaposi Sarcoma; a Case Report of an Adolescent Male with Steroid-resistant Nephrotic Syndrome - Adesina, Christiana Temilade; Raphael, Solomon; Anigilaje, Emmanuel Ademola (Journal of Pediatric Nephrology, 2018)
Although there are many reported cases of immunosuppressive-induced Kaposi sarcoma in renal transplant patients on immunosuppressive therapy, a similar report of Kaposi sarcoma among steroid-resistant nephrotic syndrome (SRNS) patients on immunosuppressive therapy is rare. This is a report of a 12-year-old Nigerian adolescent male with SRNS who developed cutaneous Kaposi sarcoma following a prolong use of cyclosporine A. This case should serve as a reminder for the possibility of malignancy development, especially Kaposi sarcoma, when SRNS patients receive cyclosporine as a steroid-sparing immunosuppressive therapy. Keywords: Steroid resistant nephrotic syndrome; cyclosporine A; Immunosuppression; Kaposi Sarcoma.